Development of Biodegradable Food Packaging Materials Based On Vegetable Leaves in Benin: Case of the Musa Sapientum Species - SEMASSOU, GUY CLARENCE; ALAKOUKO, Abdou Raimi; CHEGNIMONHAN, Kouamy Victorin (My University, 2020)
The development of biodegradable packaging is one of the environmental protection thematic. This paper presents a review of the various works relating to the development of food packaging based on the leaves of the Musa sapientum species. This review shows that Musa sapientum leaves are available, generate socio-economic benefits and have the chemical, physical, mechanical, antimicrobial and toxicity characteristics necessary for the development of biodegradable food packaging. There are also methods and standards for the manufacturing and mechanical characterisation of packaging materials based on vegetable leaves.
Keywords: Musa Sapientum; Food Packaging; Material; Vegetable Leaf; Mechanical Characterisation